2017
DOI: 10.1038/srep40066
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiles reveal gene regulation of peanut (Arachis hypogaea L.) nodulation

Abstract: The molecular mechanisms of symbiosis in cultivated peanut with a ‘crack entry’ infection process are largely understudied. In this study, we investigated the root transcriptional profiles of two pairs of non-nodulating (nod−) and nodulating (nod+) sister inbred peanut lines, E4/E5 and E7/E6, and their nod+ parents, F487A and PI262090 during rhizobial infection and nodule initiation by using RNA-seq technology. A total of 143, 101, 123, 215, 182, and 289 differentially expressed genes (DEGs) were identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 57 publications
(79 reference statements)
2
60
2
Order By: Relevance
“…To investigate the roles of auxin signalling in P. liquidambari ‐mediated activation of nodulation signalling, transcriptional response of key nodulation signalling genes SymRK , CCaMK , and early nodulin genes NIN and ENOD40 were examined at 5 and 10 dai. These two time points were chosen as nodule primordium was first observed at 10 dai in our system, and thus symbiotic signalling pathway was presumably activated in the root at 5 dai (Peng et al, ; L. Zhang, Xu, et al, ). The relative expression of all tested genes was up‐regulated in P. liquidambari and bradyrhizobium coinoculated roots compared with bradyrhizobium only inoculation roots (Figure a–d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the roles of auxin signalling in P. liquidambari ‐mediated activation of nodulation signalling, transcriptional response of key nodulation signalling genes SymRK , CCaMK , and early nodulin genes NIN and ENOD40 were examined at 5 and 10 dai. These two time points were chosen as nodule primordium was first observed at 10 dai in our system, and thus symbiotic signalling pathway was presumably activated in the root at 5 dai (Peng et al, ; L. Zhang, Xu, et al, ). The relative expression of all tested genes was up‐regulated in P. liquidambari and bradyrhizobium coinoculated roots compared with bradyrhizobium only inoculation roots (Figure a–d).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a transcriptome study showed that auxin metabolism and responses of peanut are modulated in response to bradyrhizobial invasion (Peng et al, ). However, no detail study has determined whether auxin is required for peanut–bradyrhizobium symbiosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we investigated 4,13‐diaza‐18‐crown 6 ether (Diaza18C6E) as SR for shifting the signal of perchlorate ions (ClO 4 − ). Perchlorate are anions of great interest in the field of explosives detection and environmental monitoring, which could justify the use of SR strategies for enhancing the reliability of its detection. Diaza18C6E is a crown ether‐related compound that has two secondary amino functional groups which can be protonated to form a doubly charged species.…”
Section: Resultsmentioning
confidence: 99%
“…Bradyrhizobia strain LB8 [17] was first grown from glycerol stock on YEM plate supplemented with 25 µg/ml chloramphenicol. A single colony from the plate was then grown in YEM broth in 27˚C shaker at 200 rpm until OD 600 = 0.5 -1.5.…”
Section: Rhizobia Infectionmentioning
confidence: 99%